2016
DOI: 10.18632/oncotarget.8498
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 proliferation index but not mitotic thresholds integrates the molecular prognostic stratification of lower grade gliomas

Abstract: Despite several molecular signatures for “lower grade diffuse gliomas” (LGG) have been identified, WHO grade still remains a cornerstone of treatment guidelines. Mitotic count bears a crucial role in its definition, although limited by the poor reproducibility of standard Hematoxylin & Eosin (H&E) evaluation. Phospho-histone-H3 (PHH3) and Ki-67 have been proposed as alternative assays of cellular proliferation. Therefore in the present series of 141 LGG, the molecular characterization (namely IDH status, 1p/19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Although biomarkers have demonstrated utility in the stratification of tumors by grade and in predicting the course of malignant lesions, their use in predicting the behavior of indolent tumor types has not been well assessed [13, 14, 16]. Prior studies have identified unique gene and protein expression in pathologically similar tumors located at various geographic locations [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Although biomarkers have demonstrated utility in the stratification of tumors by grade and in predicting the course of malignant lesions, their use in predicting the behavior of indolent tumor types has not been well assessed [13, 14, 16]. Prior studies have identified unique gene and protein expression in pathologically similar tumors located at various geographic locations [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic markers of interest did not show strong evidence for the ability to stratify risk among patients with IDH-mutant astrocytomas or predict WHO grade IV behavior. Larger or additional studies may provide stronger evidence in the future [6,8,12,24,30].…”
Section: Other Genetic Markersmentioning
confidence: 99%
“…In a very small biopsy, one mitosis may be sufficient, whereas in very large specimens, greater mitotic activity may be necessary [20]. These thresholds for mitotic activity have not been corroborated by several studies of IDH-mutant cohorts [12,24,33]. However, others have demonstrated that traditional grading schemes can stratify risk among patients with grade II and III IDH-mutant astrocytomas, but with ample opportunity for improvement [8,30,32].…”
Section: Mitotic Activity and Proliferation Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki-67 is now commonly used as a prognostic marker in the clinic due to its specificity for proliferating cells and ready detection in all cell cycle stages. Positive staining for Ki-67 protein [8][9][10][11][12], alongside other markers [13,14] in a patient tumour sample can be used in grading the primary tumour [15] and metastases [16]. Ki-67 staining has been reported to be of prognostic value in predicting cancer survival rates [9,17,18] and the likelihood of relapse [19].…”
Section: Introduction To Ki-67mentioning
confidence: 99%